Psychological Suggestive Connotations in Fahd Al-Askar’s Poetry: “Woman and Wine” Poem as a Model - Al-Gayam, Ismeel M. M.; Al-Rawashdeh, Basma A. S.; Essa, Ahmad H. M. Bany; Rababah, Mahmoud A. (Journal of language teaching and research, 2025)
This study explores the existentialist ideas and perspectives of the poet Fahd Al-Askar played a prominent role in challenging societal values and traditions, which he viewed as obstructing freedom and social justice. The study employed a descriptive analytical approach to analyse Al-Askar’s poetry. The results revealed that Al-Askar, as a poet with a mission, undertook the defense of his society's people, striving to spread intellectual and religious freedom. He used the themes of “woman” and “wine” as effective tools to convey his intended message. The “woman” was both a means and an end: a means to provoke societal taboos through sensual poetic descriptions, and an end to advocate women's recognition of their existence, identity, and right to participate equally in social roles alongside men. Sensual depictions served more as a pressing tool rather than an intrinsic purpose. As for “wine,” it represented another tool that Al-Askar utilized to challenge traditional societal norms. Being religiously forbidden, it served to create tension and provoke the customs of a conservative and committed society. By focusing on the central connotations of both “woman” and “wine,” Al-Askar infused them with suggestive and psychological peripheral meanings to produce the desired implications.